A Review on Highway Failure and their Maintenance - Amit Kumar; Anupam Kumar Guatam (International Journal of Scientific Research in Civil Engineering, 2024)
This study focuses on the primary objective is to determine the various factors which are responsible for the failure of the rigid pavement and also be applied the proper method of maintenance to avoid the failure problem of the road and also be evaluating the engineering properties of material used in pavement. The scope of study included the following: To identify the cause of the failure of pavement, To provide proper technique and materials of maintenance, Evaluating the engineering properties of material used in pavement.